Regulation of mRNA capping in the cell cycle. Issue 1 (2nd January 2017) - Aregger, Michael; Cowling, Victoria H.
ABSTRACT: The mRNA cap structure, which is added to nascent RNA pol II transcripts, recruits the protein complexes required for pre-mRNA transcript processing, mRNA export and translation initiation. The enzymes which catalyze mRNA cap synthesis are regulated by cellular signaling pathways which impact on their expression, localization and activity. Here we discuss the recent observation that the mRNA cap methyltransferase, RNMT, is phosphorylated on Thr-77 by CDK1-cyclin B1, which regulates its activity and the proteins with which it interacts. RNMT Thr-77 phosphorylation provides a burst of mRNA cap methyltransferase activity during early G1 phase at a time when transcription is reactivated following completion of the cell cycle. This co-ordination of transcription and mRNA capping makes an important contribution to gene expression in the cell; preventing RNMT Thr-77 phosphorylation inhibits cell proliferation. Here we discuss these findings and how mRNA cap synthesis may be regulated in other scenarios.